La voix de l’Assemblée ?Le compte rendu intégral des débats parlementaires ou quand le discours fait foi - Denis Mazzucchetti (Corela)
Some discourses have a special pragmatic status: they take the place of a former discourse, “removing” it. Such is the case with the official report (compte rendu intégral) of French Parliamentary debates, prescribed by the Constitution. Thanks to it, each citizen is supposed to know exactly what was said during a debate. This paper analyses the foundations of this belief and the ways the report serves as a substitute for previous speeches. The formal description of the official report reveals a particular type of reported speech, without mediation, associated with a kind of certification of the substitute. The aim is to distinguish between linguistic or discourse phenomena, ideological effects and social practices such as collaborative writing.